Studi Komparatif: Pandangan Ulama Mengenai Nasab sebagai Syarat Kafa’ah dalam Pernikahan - Muhammad Hafiz Fajar Hidayah; Julia Barus (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study analyzes the concept of nasab as one of the criteria for kafa'ah in marriage according to the views of scholars across madhhabs. Kafa'ah is defined as equality between husband and wife candidates in various aspects, such as religion, lineage, wealth, and social status, with the aim of creating a harmonious and sustainable household life. The research approach is conducted through a literature study with a comparative analysis method of the views of the Hanafi, Maliki, Shafi'i and Hambali madhhabs. The majority of scholars from various madhhabs recognize the importance of nasab as one of the determining elements in kafa'ah, especially to maintain family honor and stability. However, the Maliki school of thought emphasizes that equality in terms of religion and morals has more significant weight than nasab, in line with the principles of universality and human equality in Islam. This study concludes that although there are differences of opinion among scholars, they all lead to the common goal of realizing a solid marriage that is in line